2011
DOI: 10.1038/nsmb.2083
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of γ-tubulin complex protein GCP4 provides insight into microtubule nucleation

Abstract: Microtubule nucleation in all eukaryotes involves γ-tubulin small complexes (γTuSCs) that comprise two molecules of γ-tubulin bound to γ-tubulin complex proteins (GCPs) GCP2 and GCP3. In many eukaryotes, multiple γTuSCs associate with GCP4, GCP5 and GCP6 into large γ-tubulin ring complexes (γTuRCs). Recent cryo-EM studies indicate that a scaffold similar to γTuRCs is formed by lateral association of γTuSCs, with the C-terminal regions of GCP2 and GCP3 binding γ-tubulin molecules. However, the exact role of GCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 39 publications
(45 reference statements)
4
137
0
Order By: Relevance
“…Interestingly, this region is conserved down to the Xenopus laevis GCP6 orthologue Xgrip210 (Zhang et al, 2000). Whereas the grip domains were reported to be required for the interaction between GCPs and ctubulin during complex formation, the interface between the two conserved domains is assumed to form a flexible hinge in GCP3 (Guillet, 2011;Kollman et al, 2008). Conformational changes in this flexible region, which might be regulated by posttranslational modifications, were suggested to be required for triggering the microtubule-nucleating activity of the c-TuRC (Guillet, 2011;Kollman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this region is conserved down to the Xenopus laevis GCP6 orthologue Xgrip210 (Zhang et al, 2000). Whereas the grip domains were reported to be required for the interaction between GCPs and ctubulin during complex formation, the interface between the two conserved domains is assumed to form a flexible hinge in GCP3 (Guillet, 2011;Kollman et al, 2008). Conformational changes in this flexible region, which might be regulated by posttranslational modifications, were suggested to be required for triggering the microtubule-nucleating activity of the c-TuRC (Guillet, 2011;Kollman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the grip domains were reported to be required for the interaction between GCPs and ctubulin during complex formation, the interface between the two conserved domains is assumed to form a flexible hinge in GCP3 (Guillet, 2011;Kollman et al, 2008). Conformational changes in this flexible region, which might be regulated by posttranslational modifications, were suggested to be required for triggering the microtubule-nucleating activity of the c-TuRC (Guillet, 2011;Kollman et al, 2008). Because the majority of Plk4 phosphorylation sites were identified in a corresponding region between the grip1 and grip2 domains of GCP6, including the repeat region, it is tempting to speculate that a phosphorylation of GCP6 by Plk4 activates centriolar microtubule nucleation and thereby procentriole formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly conserved sequences in GCPs 2-6 were initially described as c-tubulin ring protein (Grip) motifs (Gunawardane et al, 2000), but the sequence similarity extends beyond these motifs and, on the basis of insight obtained from the GCP4 crystal structure, we will refer to the conserved regions as N-and C-terminal 'Grip domains' (Fig. 1A) (Guillet et al, 2011). More-recent studies have identified Fig.…”
Section: Molecular Composition Of Cturcsmentioning
confidence: 99%
“…1A), and that GCP4, GCP5 and GCP6 might be part of the cTuRC ring structure by substituting for GCP2 or GCP3 at specific positions to function, for example, as ring assembly initiators or terminators (Fig. 1B) (Guillet et al, 2011;Kollman et al, 2011).…”
Section: Grip-gcpsmentioning
confidence: 99%